Оборотни в законе. Когда терпение лопается: роман / К. Казанцев - Казанцев Кирилл (Оборотни в законе, 2009)
Экземпляры: (20201111) / Инвентарный номер: 34417 / Цена: 206.00 / Сис.шифр: Р2 / Авт.знак: К 14 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6